Debating Vivekananda : a reader - Raghuramaraju, A. (O. U. P, 2014)
By conferring titles such as Swami, Yogi, Mahatma, Maharshi, Gurudev or Baba, the Indian society has transformed several writers and thinkers of modern India into icons. It is not surprising therefore that a profusion of hagiographic and emotional writings exist on the renowned nineteenth-century philosopher Swami Vivekananda and hence the pressing need to look at him in the light of debates in academic writings in order to enrich the liberal academic space.